Designing knowledge-matching facilities for scaling climate-smart agriculture: A proposal for accelerating food systems’ transformation in a changing climate - Koerner, Jana; Dinesh, Dhanush; Nagano, Akiko (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The brief talks about designing knowledge-matching facilities for scaling climate-smart agriculture. This is a priority discussed in the International Workshop on Scaling up and out of Climate-smart Technologies and Practices for Sustainable Agriculture (an initiative initiating from 2019-MACSG20), as well as of numerous CCAFS partners in the governments, research, donor, financial and policy institutions, civil society and private sectors. CCAFS proposes to join efforts, and outlines a way forward to develop and/or shape knowledge matching facilities for accelerating food systems transformation in a changing climate. This document is intended to be a living document that informs members and interested stakeholders about intermediate results and the planned or next steps.